KAJIAN KARAKTERISTIK SOSIAL, EKONOMI DAN BUDAYA MASYARAKAT ADAT SEKITAR KELOMPOK HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON PROVINSI MALUKU - Sitanala, Merlin Renny; Parera, Evelin; Parera, Lydia (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study aims to analyze the social, economic and cultural characteristics of the community around the Mount Sirimau Protected Forest Group in Ambon City, Maluku Province. In this study, we use an interdisciplinary approach to understand the relationship between humans and the environment in the region. Data was collected through field surveys, interviews and literature studies. The results of the analysis show that communities around protected forests have a high dependence on natural resources provided by these forests as their main source of livelihood. They also have a rich culture, with a diversity of traditions, beliefs and cultural practices deeply rooted in their daily lives. However, this study also reveals the social and economic challenges faced by society, including limited access to public services and income inequality. The importance of community participation in protected forest management is also highlighted in this study. In conclusion, this study emphasizes the importance of a holistic approach in protected forest management, which takes into account social, economic, cultural and ecological aspects. Collaboration between government, non-government organizations and local communities is needed to formulate sustainable strategies to preserve protected forests and improve the welfare of surrounding communities.